The Medina Embolic Device: early clinical experience from a single center - Aguilar Pérez, Marta; Bäzner, Hansjörg (Journal of neuroInterventional surgery, 2017)
Objective: To report our initial experience with the Medina Embolic Device (MED) in unruptured intracranial aneurysms either as sole treatment or in conjunction with additional devices. Methods: 15 consecutive patients (6 women, 9 men) with unruptured aneurysms were treated between September 2015 and April 2016. The aneurysm fundus measured at least 5 mm. We evaluated the angiographic appearances of treated aneurysms at the end of the procedure and at follow-up, the clinical status, complications, and requirement for adjunctive devices. Results: The MED was successfully deployed in all but one case and adjunctive devices were required in 10 cases. Aneurysm locations were middle cerebral artery bifurcation (n=3), internal carotid artery (ICA) bifurcation (n=1), supraclinoid ICA (n=5), posterior communicating artery (n=1), anterior communicating artery (n=2), cavernous ICA (n=2), distal basilar sidewall (n=1), basilar tip (n=1). Three patients had complications although none could be attributed to the MED. Immediate angiographic results were modified Raymond-Roy classification (mRRC) I=1, mRRC II=5, mRRC IIIa=3, mRRC IIIb=5, and one patient showed contrast stasis within the fundus of the aneurysm. Follow-up angiography was available in 11 patients, with four showing complete aneurysm exclusion, six with stable remnants and one patient with an enlarging neck remnant. Conclusions: The MED represents a major step forward in the treatment of intracranial aneurysms. It can result in rapid exclusion of an aneurysm from the circulation and has a good safety profile. We believe that the true value of the MED will be in combining its use with adjunctive devices such as endoluminal flow diverters that will result in rapid aneurysmal exclusion.